Respiratory symptom and disorder characteristic of farmer who exposed by pesticide - Candrawati, Ni Wayan; Ngurah Rai, Ida Bagus; Agung Krisdanti, I Desak Putu; Andrika, Putu; Kinanti, Diah Permata; Sujana, I Putu Surya; Widiasari, Ni Putu Ayu; Sri Adiputri, Kadek (International Journal of Advances in Medicine, 2023)
Background: Pesticide is related to respiratory diseases; thus, personal protective equipment is very important as a preventive equipment while using pesticide. However, farmers in Indonesia still rarely use PPE when farming for reasons of inconvenience and availability problems. Methods: This study was an analytic observational study with cross-sectional design. Sampling technique was consecutive sampling. Subject was 62 residents of Sukawana Village, Kintamani, Bangli who work as farmers and used pesticides. Results: Dominant subject never experienced chronic respiratory symptom. The spirometry results showed mean of FVC (L) was 3.50 liters, FVC% was 93.31%, FEV1 (L) was 3.09, FEV1% was 97.64%, FEV1/FVC was 88.72, FEF 25-75% (L/s) was 4.07 liters/second, and FEF 25-75% was 106.95%. Age was significantly related to the occurrence of wheezing but not significantly related to another. Older people have significantly lower mean of FVC (L), FEV 1 (L), and FEF 25-75% (L/s) than younger. Smokers have significantly higher mean of FVC (L) and FEF 25-75% (L/s) than non-smokers. Conclusions: The dominant subject never experienced chronic respiratory symptom with spirometry mean values within normal limits. Age was significantly related to the occurrence of wheezing. Older age has significantly lower mean of FVC (L), FEV 1(L), and FEF 25-75% (L/s).